Probiotic administration modifies the milk fatty acid profile, intestinal morphology and intestinal fatty acid profile of goats - Apas, Ana Lidia (2015)
The effect of a mixture of potentially probiotic bacteria (MPPB; Lactobacillus reuteri DDL 19; Lactobacillus alimentarius DDL 48; Enterococcus faecium DDE 39; and Bifidobacterium bifidum strains) on milk fatty acid (FA) profile with emphasis on cis9, trans11 conjugated linoleic acid (CLA) in the middle stage of goat lactation was determined. In addition, the effects of MPPB feeding on FA profile in intestinal content and intestinal morphology in weaned goats were analyzed. The probiotic supplement was able to modify FA composition of milk and intestinal content. The unsaturated FA concentrations in milk (g of FA/L of milk)e increased from 4.49 to 7.86 for oleic (18:1), from 0.70 to 1.39 for linoleic (18:2), from 0.063 to 0.187 for linolenic (18:3) acids, and from 0.093 to 0.232 for CLA. The atherogenicity index diminished 2-fold after MPPB ingestion. In the intestinal content of the weaned goats, no significant difference in saturated FAs compared to the control was observed. However, oleic acid, linolenic acid, CLA, and docosahexaenoic acid (DHA) concentrations increased by 81, 23, 344, and 74%, respectively, after probiotic consumption. The ruminal production of CLA was increased by the MPPB. However, bacterial strains of MPPB were unable to produce CLA in culture media.By histological techniques, it was observed that the treated group had intestinal more conserved morphological structures than the control group. The results obtained in this study indicate that the MPPB administration in lactating and weaned goats allows for the production of milk with improved concentrations of beneficial compounds, and also produces a protective effect in goat intestine. The results obtained in this study reinforce the strategy of probiotics application to enhance goat health with the production of milk with higher concentration of polyunsaturated FA.